2022
DOI: 10.1101/2022.09.07.507051
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A multiplexed plant-animal SNP array for selective breeding and species conservation applications

Abstract: Reliable and high-throughput genotyping platforms are of immense importance for identifying and dissecting genomic regions controlling important phenotypes, supporting selection processes in breeding programmes, and managing wild populations and germplasm collections. Amongst available genotyping tools, SNP arrays have been shown to be comparatively easy to use and generate highly accurate genotypic data. Single species arrays are the most commonly used type so far; however, some multi-species arrays have been… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…A total of 6,884 SNP marker assays were considered high quality with two to three distinct genotype clusters from the multi‐species Affymetrix SNP array (Montanari et al, 2022). The WGS of 210 accessions identified a total of 4,905,377 SNP and indel variants.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 6,884 SNP marker assays were considered high quality with two to three distinct genotype clusters from the multi‐species Affymetrix SNP array (Montanari et al, 2022). The WGS of 210 accessions identified a total of 4,905,377 SNP and indel variants.…”
Section: Resultsmentioning
confidence: 99%
“…The WGS of 210 accessions identified a total of 4,905,377 SNP and indel variants. Subsequently, 5,886 SNPs from the SNP array (Montanari et al, 2022) were identified that had corresponding biallelic SNP calls with matching alleles in the WGS dataset (File S2). The WGS variant calls were used to assess genotype segregation and missing genotype call rates for the 131 R. idaeus accessions at the 5,886 validated array SNP sites.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The array containing 9002 SNPs for mānuka was described by Montanari et al . (2023), and the genotyping was performed by Labogena (Jouy‐en‐Josas, France) using standard protocols. After genotyping, the SNP data were analysed using the A xiom A nalysis S uite v.5.1.1 software applying a dish QC threshold of 0.82 and a QC Call Rate > 95%.…”
Section: Methodsmentioning
confidence: 99%
“…In total, 185 individuals from the EC201 9 EC103 segregating population were screened using an Affymetrix Axiom TM (Thermo-Fisher Scientific, Waltham, MA, USA) Single Nucleotide Polymorphism (SNP) array. The array containing 9002 SNPs for m anuka was described by Montanari et al (2023), and the genotyping was performed by Labogena (Jouy-en-Josas, France) using standard protocols. After genotyping, the SNP data were analysed using the AXIOM ANALYSIS SUITE v.5.1.1 software applying a dish QC threshold of 0.82 and a QC Call Rate > 95%.…”
Section: Determination Of Transcript Abundance In Six Tissue Typesmentioning
confidence: 99%